2021
DOI: 10.7717/peerj.12277
|View full text |Cite
|
Sign up to set email alerts
|

The correlation of WDR76 expression with survival outcomes and immune infiltrates in lung adenocarcinoma

Abstract: Background WD repeat domain 76 (WDR76) is a predicted member of the WD40-repeat-containing domain superfamily and possibly involves in various biological processes, but its function in cancers is poorly characterized. This study aimed to evaluate the role of WDR76 in the prognosis and immune infiltrates of lung adenocarcinoma (LUAD). Methods WDR76 expressions in LUAD tissues and normal tissues were primarily compared by The Cancer Genome At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Similar results have also confirmed that WDR76 causes instability of the RAS in CRC, impairing the proliferation and activation of cancer stem cells by inhibiting the Wnt/β-catenin signaling pathway [ 12 ]. Nevertheless, an opposing argument claims that WDR76 specifically acts as an oncogenic factor in lung adenocarcinoma, which is an independent risk factor for prognosis, and that high expression of WDR76 is significantly associated with immune cell infiltration, thereby participating in tumor immunity [ 13 ]. These controversial results illustrate the complexity of WDR76 function in different cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have also confirmed that WDR76 causes instability of the RAS in CRC, impairing the proliferation and activation of cancer stem cells by inhibiting the Wnt/β-catenin signaling pathway [ 12 ]. Nevertheless, an opposing argument claims that WDR76 specifically acts as an oncogenic factor in lung adenocarcinoma, which is an independent risk factor for prognosis, and that high expression of WDR76 is significantly associated with immune cell infiltration, thereby participating in tumor immunity [ 13 ]. These controversial results illustrate the complexity of WDR76 function in different cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that uncontrollable immune dysfunction promotes the occurrence and development of cancer 29,30 . The inextricable link between lung cancer and immune infiltration has been repeatedly demonstrated 31‐33 . However, the association between immune infiltration and RAGE expression has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“… 29 , 30 The inextricable link between lung cancer and immune infiltration has been repeatedly demonstrated. 31 , 32 , 33 However, the association between immune infiltration and RAGE expression has not been reported. In the present study, GO‐BP enrichment analysis indicated that these co‐expressed genes of RAGE were implicated in the immune‐related pathways, including neutrophil activation involved in immune response, neutrophil degranulation, and regulation of leukocyte‐mediated immunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used nonlinear dimension reduction (t-distributed stochastic neighbour embedding; t-SNE) clustering and the "FindAllMarkers" function (parameters: minimum% = 0:3, log function threshold = 0:25) to identify marker genes based on between-cluster differences. The cell clusters were then annotated based on reported cellspecific marker genes [23][24][25][26][27][28][29].…”
Section: Methodsmentioning
confidence: 99%